5‐(4‐Methoxybenzylidene)thiazolidine‐2, 4‐dione‐derived VEGFR‐2 inhibitors: Design, synthesis, molecular docking, and anticancer evaluations. Issue 9 (9th June 2020) - El‐Adl, Khaled; Sakr, Helmy; Nasser, Mohamed; Alswah, Mohamed; Shoman, Fatma M. A.
Abstract: A novel series of 5‐(4‐methoxybenzylidene)thiazolidine‐2, 4‐dione derivatives, 5a–g and 7a–f, was designed, synthesized, and evaluated for their anticancer activity against HepG2, HCT116, and MCF‐7 cells. HepG2 and HCT116 were the most sensitive cell lines to the influence of the new derivatives. In particular, compounds 7f, 7e, 7d, and 7c were found to be the most potent derivatives of all the tested compounds against the HepG2, HCT116, and MCF‐7 cancer cell lines. Compound 7f (IC50 = 6.19 ± 0.5, 5.47 ± 0.3, and 7.26 ± 0.3 µM, respectively) exhibited a higher activity than sorafenib (IC50 = 9.18 ± 0.6, 8.37 ± 0.7, and 5.10 ± 0.4 µM, respectively) against HepG2 and MCF‐7, cells but a lower activity against HCT116 cancer cells, respectively. Also, this compound displayed a higher activity than doxorubicin (IC50 = 7.94 ± 0.6, 8.07 ± 0.8, and 6.75 ± 0.4 µM, respectively) against HepG2 and MCF‐7 cells, but nearly the same activity against HCT116 cells, respectively. All derivatives, 5a–g and 7a–f, were evaluated for their inhibitory activities against vascular endothelial growth factor receptor‐2 (VEGFR‐2). Among them, compound 7f was found to be the most potent derivative that inhibited VEGFR‐2 at an IC50 value of 0.12 ± 0.02 µM, which is nearly the same as that of sorafenib (IC50 = 0.10 ± 0.02 µM). Compounds 7e, 7d, 7c, and 7b exhibited the highest activity, with IC50 values of 0.13 ± 0.02, 0.14 ± 0.02, 0.14 ± 0.02, and 0.18 ± 0.03 µM, respectively, which are more than the half of that of sorafenib. Furthermore, molecular docking was performed to investigate their binding mode and affinities toward the VEGFR‐2 receptor. The data obtained from the docking studies highly correlated with those obtained from the biological screening. Abstract : A novel series of 5‐(4‐methoxybenzylidene)thiazolidine‐2, 4‐dione derivatives (5a–g and 7a–f ) was designed, synthesized, and evaluated for their anticancer activity against HepG2, HCT116, and MCF‐7 cells and for their inhibitory activities against vascular endothelial growth factor receptor‐2 (VEGFR‐2). Compound 7f turned out to be the most potent derivative, inhibiting VEGFR‐2 at an IC50 value of 0.12 ± 0.02 µM, which is comparable to sorafenib (IC50 = 0.10 ± 0.02 µM). Molecular docking was performed to investigate the binding mode and affinities toward the VEGFR‐2 receptor.